Laser treatment for facial acne scars: A review. (17th November 2018) - Sadick, Neil S.; Cardona, Andrea
ABSTRACT: Background and Objectives : Acne scarring is a widely prevalent condition that can have a negative impact on a patient's quality of life and is often worsened by aging. A number of options are available for the treatment of acne scarring, including retinoids, microdermabrasion, dermal fillers, and surgical techniques such as subcision. The aim of this review is to evaluate the different laser modalities that have been used in peer-reviewed clinical studies for treatment of atrophic acne scars, and summarize current clinical approaches. Materials and Methods : A Medline search spanning from 1990 to 2016 was performed on acne scarring. Search terms included "atrophic acne scars, " "ablative'', "nonablative, " "fractional, " "nonfractional, " "neodymium, " "alexandrite, " "pulsed dye" lasers, and results are summarized. Results : Various types of lasers have been evaluated for the treatment of atrophic acne scars. While they are efficacious overall, they differ in terms of side effects and clinical outcomes, depending on patients skin and acne scar type. A new emerging trend is to combine lasers with other energy-based devices and/or topicals. Conclusion : Evaluation of the literature examining acne scar treatment with lasers, revealed that clinical outcomes are dependent on various patient factors, including atrophic acne scar subtype, patient skin type, treatment modality, and side-effect profile.